KONFLIK PEMANFAATAN LAHAN DI SEPANJANG SEMPADAN SUNGAI DI TUKAD PAKERISAN, GIANYAR, BALI - I Gusti Putu Anindya Putra; I Nyoman Harry Juliarthana; Komang Dody Tri Anggara Putra (Pranatacara Bhumandala: Jurnal Riset Planologi, 2022)
The purpose of this research is to understand deeply related to land use conflicts along the Tukad Pakerisan river border. This study uses a descriptive method that produces descriptive data from the person or object being observed. For the discussion of data analysis carried out inductively. The observative-descriptive method in this study was carried out by observing changes in the pattern of river border land use in Tukad Pakerisan. The results of this study indicate that the conflict in the use of space that occurs along the Tukad Pakerisan border occurs between the use as a tourist attraction and the socio-cultural function of the community for rituals and sacred areas. Conflicts of interest in land use in the Tukad Pakerisan river border area occur due to the growing development of tourism activities, coupled with the ease with which investors obtain permits to construct buildings along the Tukad Pakerisan river border, especially in Pejeng Kelod Village, so that land conversion often occurs for the benefit of tourism accommodation. which will lead to conflicts over land use in the Tukad Pakerisan River Border area.